2020
DOI: 10.2147/rmhp.s280214
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge of Child Health and Affecting Factors Among Preschool Teachers: A Cross-Sectional Study in Chongqing, China</p>

Abstract: Aim This research aims to explore the health knowledge mastery of preschool teachers in Chongqing. Methods A cross-sectional questionnaire survey of preschool teachers in Chongqing was conducted by random sampling. A total of 399 preschool teachers were included in this research. Multiple linear regression analysis was conducted to explore the influencing factors on preschool teachers’ mastery of preschool child health knowledge. Results This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
4
0
2
Order By: Relevance
“…For example, one recent study in China showed insufficient knowledge of teachers both in the sphere of children's health and in the health education issues. The researchers assert that both education and work experience are not guarantees of adequate preparation in health education (Hu et al, 2020). Similar results were found by Spanish researchers stating that even though Health Education is included in the Early Childhood Education curriculum, teachers do not manage to develop it effectively (Llorent-Bedmar & Cobano-Delgado, 2019).…”
Section: Discussionsupporting
confidence: 55%
“…For example, one recent study in China showed insufficient knowledge of teachers both in the sphere of children's health and in the health education issues. The researchers assert that both education and work experience are not guarantees of adequate preparation in health education (Hu et al, 2020). Similar results were found by Spanish researchers stating that even though Health Education is included in the Early Childhood Education curriculum, teachers do not manage to develop it effectively (Llorent-Bedmar & Cobano-Delgado, 2019).…”
Section: Discussionsupporting
confidence: 55%
“…It is crucial to make teachers and parents aware that these practices can help to check the growing ill-effects of lockdown. 33,48 Restriction of online classes with breaks in between sessions, promoting (permitted) outdoor activities, encouraging “family” time with non-gadget-based learning and entertainment are some measures that can be adopted. Favoring care to those of higher socioeconomic means, those with better access to care, and perhaps even of different race groups, is also a priority 49 to make care more equitable.…”
Section: What Is Newmentioning
confidence: 99%
“…Status kesehatan anak prasekolah saat ini terancam, karena setidaknya ada 41 juta anak di bawah usia 5 tahun yang kelebihan berat badan atau obesitas di dunia. Salah satu bukti nyata adalah adanya kenaikan tingkat obesitas anak usia 0-7 tahun di China yang mencapai angka 6% (Hu et al, 2020). Jumlah anak obesitas ini diperkirakan akan meningkat menjadi 6,64 juta pada tahun 2030 (Ma & Zhang, 2019).…”
Section: Pendahuluanunclassified